2011
DOI: 10.1007/s10803-011-1217-x
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Burden Among Individuals with Autism

Abstract: The objective of this study was to assess the inpatient care burden among individuals with autism using the 2007 Health Care Utilization Project Nationwide Inpatient Sample [HCUP-NIS]). There were ~26,000 hospitalizations among individuals with autism in 2007, with an overall rate of 65.6/100,000 admissions. Rates of hospitalizations were the highest among individuals with autism aged 10-20 years, males, having household income >$63,000, and with private insurance, respectively. In terms of hospital characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 15 publications
2
51
3
1
Order By: Relevance
“…Around one-third of ED visits among adults with ASD led to an inpatient admission as compared to one-tenth of adults without ASD. This indicates that higher ED use among adults with ASD may also lead to greater hospitalization rates which is associated with high hospitalization costs (Lokhandwala et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Around one-third of ED visits among adults with ASD led to an inpatient admission as compared to one-tenth of adults without ASD. This indicates that higher ED use among adults with ASD may also lead to greater hospitalization rates which is associated with high hospitalization costs (Lokhandwala et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the independent effect of preterm birth on hospitalisation rates after 1 year of age is both an increase in frequency and earlier median age at hospitalisation, and this is consistent across all case groups. Recent studies in the USA 17 and Denmark 22 have investigated the hospitalisation burden for children with autism, and found that individuals with autism had significantly higher lengths of stay and that costs were considerably more than for those without autism. The Danish study also found that children with ASD had an increased rate of contact with the hospital, regardless of the cause of their hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…15 Therefore, it is not surprising that children with ASD also often experience medical conditions such as epilepsy, bowel dysfunction and autoimmune disorders 16 and that their burden of hospitalisation is considered to be high. 17 Differences in healthcare policies and pathways of care may impact on hospitalisation rates and service use for children with developmental disorders over time. 8 18 For example, a recent Canadian study using administrative data 19 found that those with intellectual or developmental disabilities were more likely than those without to use emergency department services.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…For certain complex medical conditions, such as cystic fibrosis, diabetes, and sickle cell disease, children with physical illness and a comorbid mental health condition have higher hospital utilization than children with no mental health condition. 8 -11 In addition, children with attention-deficit/hyperactivity disorder (ADHD) 12 -15 depression 16 or autism 17,18 have higher rates of hospitalizations and health care costs compared with children without these mental health conditions. Nevertheless, little is known about the epidemiology of co-occurring mental health conditions in pediatric medical and surgical hospitalizations and how comorbid mental health conditions may affect hospital resource utilization.…”
Section: What This Study Addsmentioning
confidence: 99%